Auto-learning TSN: improvements on TSN usability - Tongtong WANG; Jiayi ZHANG; Lihao CHEN; Xuesong GENG (Dianxin kexue)
Many network applications (e.g., industrial control) require networks to provide deterministic transmission services, and traditional statistical multiplexing networks can not meet the needs of this type of applications.IEEE 802.1 TSN standard and related research can provide deterministic networking services over Ethernet.The basic principles of TSN were described briefly, the key queuing mechanisms of TSN by using network calculus were analyzed quantitatively, and an auto-learning TSN mechanism was proposed to adaptively support non-TSN device connections by network intelligence.Together with delay guarantee algorithms, a E2E TSN solution can be formed and used for the further promotion and application of TSN technology.